MANFAAT PENGGUNAAN DATABASE DALAM PENINGKATAN LAYANAN PERPUSTAKAAN UIN SUMATERA UTARA - Chairane; Adinda Puan; Rahmat Syahputra; Thia Thania Aldine; Nurbaiti (CV. ALIM'SPUBLISHING, 2023)
The database or what is commonly referred to as a database is a collection of data that is stored neatly, structured on a computer and is very important in an information system. The database functions as a provider of information for its consumers. The database has many benefits, some of which are facilitating data management, data accuracy, increasing productivity, cost savings, as a material for making better decisions and helping to maintain data security. The purpose of thisresearch is to understand what are thebenefits of databases and how to implement databases for organizations or companies. By knowing the benefits of a database, an organization or company can make good decisions or policies in managing andutilizing their data. The method in this study uses a qualitative method by conducting a survey to find out the benefits of the database at the UIN North Sumatra Library and what facilities are obtained by implementing the database in managingits information system. The results obtained from this study are that the North Sumatra Uin Library utilizes databases in improving services by carrying out several developments such as an online library, an application called OPAC, an application that makes it easy to check library collections and a web called repository which is a collection application. the work of students. Libraries that previously only used the recording method but have switched to using online by utilizing databases.